2008
DOI: 10.1021/jf801104e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Altitudinal Variation on the Content of Phenolic Compounds in Wild Populations of Calluna vulgaris, Sambucus nigra, and Vaccinium myrtillus

Abstract: This study deals with the effect of altitudinal variation on the content of phenolic compounds in three traditional herbal plants, which are also consumed as food in Central Europe. Herbs of Calluna vulgaris (L.) HULL, flowers and fruits of Sambucus nigra L., and berries of Vaccinium myrtillus L. collected in the Naturpark Solktaler (Austria) were extracted using accelerated solvent extraction (ASE). Identification and quantification of the constituents in the polar extracts (methanol 80%, v/v) were achieved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
97
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 31 publications
12
97
4
Order By: Relevance
“…S. nigra consisted mainly of caffeic acid (913.19 µg/g), with lesser amounts of vanilic acid (299.38 µg/g), gallic acid (176.61 µg/g), and cinnamic acid (7.98 µg/g). Curiously, these results contrast to that of Rieger et al [31]. In their work, the caffeic acid was not detected in S. nigra; instead, they found rutin in high amounts, which we did not detect.…”
Section: Resultscontrasting
confidence: 99%
“…S. nigra consisted mainly of caffeic acid (913.19 µg/g), with lesser amounts of vanilic acid (299.38 µg/g), gallic acid (176.61 µg/g), and cinnamic acid (7.98 µg/g). Curiously, these results contrast to that of Rieger et al [31]. In their work, the caffeic acid was not detected in S. nigra; instead, they found rutin in high amounts, which we did not detect.…”
Section: Resultscontrasting
confidence: 99%
“…Several experimental data support that enhanced solar, UV-B radiation is correlated to accumulation of highly antioxidative flavonoids (Jaakola et al, 2004;Markham et al, 1998;Spitaler et al, 2006). Previously, we showed that flavonols revealed significant differences in samples of Calluna vulgaris L. (Ericaceae) collected at different altitudes with increased levels of quercetin glycosides at higher altitudes whereas no significant correlation could be found for caffeoyl quinic acids and the dihydroflavonol glycoside callunin ( However, in the current study, we could not confirm the assumption that only the content of flavonol 3-Oglycosides with adjacent hydroxyl groups in ring B rise with increasing altitude (Ganzera et al, 2008b;Rieger et al, 2008) as also for compounds 11 and 13 a similar trend as for compound 12 was observed. Ganzera et al (2008a) showed that external factors like altitude and temperature had an effect on the secondary metabolites in Arnica montana L. (Asteraceae).…”
Section: Total Content Of Flavonoids and Phenolicscontrasting
confidence: 90%
“…nigra flowers there are a few publications on their phenolic composition but from other countries, such as France (Froehlicher et al, 2009) for C. monogyna, Austria (Rieger et al, 2008), Denmark (Christensen et al, 2008;Kaack and Christensen, 2010) and Poland For S. nigra, all the previous studies reported the presence of quercetin-3-O-glucoside (isoquercitrin) and quercetin-3-O-rutinoside (rutin), as well as different caffeoylquinic acids, as also observed in the present study (Christensen et al, 2008;Rieger et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…C. monogyna (Froehlicher et al, 2009) andS. nigra (Dawidowicz et al, 2003;Rieger et al, 2008;Christensen et al, 2008;Kaack and Christensen, 2010) flowers were studied, but with plant material from other European countries, i.e not growing under…”
Section: Introductionmentioning
confidence: 99%